Downregulation of Immunosuppressive Molecules, PD-1 and PD-L1 but not PD-L2, in the Patients with Multiple Sclerosis - Mohammad Reza Javan (Iranian Journal of Allergy, Asthma and Immunology, 2016)
Programmed cell death-1 (PD-1) and its ligands, PD-L1 and PD-L2, have been regarded as important immune system regulatory molecules. The aberrant expression of the molecules has been related to several autoimmune disorders. This study is aimed to assess the mRNA expression level of PD-1, PD-L1, and PD-L2 molecules in the peripheral blood mononuclear mells (PBMCs) from multiple sclerosis (MS) patients. PBMCs were isolated from the whole blood of 50 MS and 50 healthy individuals. Total RNA content of the leukocytes was extracted. Then, cDNA was synthesized from the extracted RNA. Afterwards, quantitative analysis of PD-1, PD-L1 and PD-L2 was carried out through Real Time PCR using the TaqMan gene expression assays. Relative expression of PD-1 and PD-L1 in PBMCs from MS patients was significantly lower compared with the healthy control group (p=0.003 and 0.012, respectively). However, no significant difference was observed in the expression level of PD-L2 between patients and healthy individuals. Relative expression of PD-1 correlated with expanded disability status scale score (EDSS) of the patients (r=-0.763, p=0.008). Downregulation of the immunosuppressive molecules, PD-1 and PD-L1, may imply that over-activation of immune cells in multiple sclerosis occurs through signaling dysfunction of these molecules and PD-L2 plays no important role in this context.